2021
DOI: 10.1016/j.bonr.2021.101067
|View full text |Cite
|
Sign up to set email alerts
|

Chondrodysplasia, enchondromas and a chest deformity causing severe pulmonary morbidity in a boy with a PTHLH duplication: A case report

Abstract: Parathyroid hormone-like hormone (PTHLH) plays an important role in bone formation. Several skeletal dysplasias have been described that are associated with disruption of PTHLH functioning. Here we report on a new patient with a 898 Kb duplication on chromosome 12p11.22 including the PTHLH gene. The boy has multiple skeletal abnormalities including chondrodysplasia, lesions radiographically resembling enchondromas and posterior rib deformities leading to a severe chest deformity. Severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Some pathogenic variants in the PTHLH gene may cause a specific pattern of short stature accompanied by other clinical features such as oligodontia, delayed tooth eruption, and variable middle or distal phalangeal anomalies. Delayed bone age and chest deformities have been also reported (11,13) . These phenotypic features seem to be concordant with brachymesophalangia II and V type A4, dental anomalies, and thoracic anomalies in our patient.…”
Section: Discussionmentioning
confidence: 96%
“…Some pathogenic variants in the PTHLH gene may cause a specific pattern of short stature accompanied by other clinical features such as oligodontia, delayed tooth eruption, and variable middle or distal phalangeal anomalies. Delayed bone age and chest deformities have been also reported (11,13) . These phenotypic features seem to be concordant with brachymesophalangia II and V type A4, dental anomalies, and thoracic anomalies in our patient.…”
Section: Discussionmentioning
confidence: 96%
“…Flöttmann et al reported on a three-generation pedigree with short humerus, curved radius, and a specific type of severe brachydactyly with features of types E and A1 but without the enchondromatosis and AO hitherto described [ 22 ]. Finally, Tacke et al reported on a patient with multiple skeletal abnormalities including chondrodysplasia, lesions radiographically resembling enchondromas and posterior rib deformities leading to a severe chest deformity [ 23 ]. No AO was observed in this patient (probably not yet present owing to the young age of the patient compared to the other observations).…”
Section: Discussionmentioning
confidence: 99%